2018
DOI: 10.1021/acsnano.8b04265
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Defect-Related Raman Mode of Monolayer WS2 via Tip-Enhanced Resonance Raman Scattering

Abstract: Monolayer tungsten disulfide (WS) has emerged as an active material for optoelectronic devices due to its quantum yield of photoluminescence. Despite the enormous research about physical characteristics of monolayer WS, the defect-related Raman scattering has been rarely studied. Here, we report the correlation of topography and Raman scattering in monolayer WS by using tip-enhanced resonance Raman spectroscopy and reveal defect-related Raman modes denoted as D and D' modes. We found that the sulfur vacancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 42 publications
8
92
0
Order By: Relevance
“…Several studies have emphasized the potential of Raman spectroscopy to study the effect of doping and defects 17,18 , as well as to measure strain in many 2D materials, including MoS 2 19,20 . Even the subwavelength defects can be characterized by tip-enhanced Raman spectroscopy [21][22][23][24][25][26][27] , which enables Raman analysis with a nanoscale spatial resolution, using near-field light generated at a metallic nanotip through plasmon resonance [28][29][30][31][32][33][34] . Widely studied Raman modes of MoS 2 are the high-frequency modes, E 2g and A 1g , which arise due to the in-plane and the out of plane vibrations of atoms within each layer, respectively.…”
Section: Openmentioning
confidence: 99%
“…Several studies have emphasized the potential of Raman spectroscopy to study the effect of doping and defects 17,18 , as well as to measure strain in many 2D materials, including MoS 2 19,20 . Even the subwavelength defects can be characterized by tip-enhanced Raman spectroscopy [21][22][23][24][25][26][27] , which enables Raman analysis with a nanoscale spatial resolution, using near-field light generated at a metallic nanotip through plasmon resonance [28][29][30][31][32][33][34] . Widely studied Raman modes of MoS 2 are the high-frequency modes, E 2g and A 1g , which arise due to the in-plane and the out of plane vibrations of atoms within each layer, respectively.…”
Section: Openmentioning
confidence: 99%
“…Tip-enhanced Raman spectroscopy (TERS) can simultaneously provide the high spatial resolution and chemical sensitivity needed for materials and device characterisation at the nanoscale through the highly confined enhanced electromagnetic field generated within a plasmonic nano-cavity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It has recently been demonstrated that TERS systems based on a scanning tunnelling microscope (STM) can obtain impressive images and information with subnanometre resolution, [10][11][12] but these systems are restricted to special extreme environments (e.g. ultra-high vacuum and low temperature) that are not suitable to study the asfabricated electrical and mechanical properties of devices.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast value can be determined by obtaining the intensity ratio of both the 2LA(M) peaks depicted in Figure 5b, and the value of the TERS enhancement factor can be calculated using the obtained contrast value, radius of the laser spot, and measured R tip . The defined equations for both the contrast and enhancement factor are represented as follows [7,22,34]:…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, fabricating a sharp nanotip is critical to improving the spatial resolution of a TERS image. TERS, which is a powerful tool, not only produces Raman scattering images with high spatial resolution but also has a significantly enhanced Raman signal, thereby enabling various low-dimensional materials to be investigated [7][8][9][10]. A sharp Au tip can be implemented as both a probe for scanning probe microscopy and a source of near-field light, owing to the localized surface plasmon resonance (LSPR).…”
Section: Introductionmentioning
confidence: 99%